Avaliação das interferências da disposição de resíduos de fossas e tanques sépticos em lagoas de estabilização que tratam lixiviados: estudo de caso para o aterro sanitário de Anápolis (GO) - Carrilho, Samara Monayna Alves Vasconcelos (2014)
The destination of septage has resulted in environmental and public health problems, due especially to the lack of adequate alternatives for its destination and of closer, more rigorous monitoring. The problem worsens in areas lacking sewage treatment plants, since the disposal in such systems has been the most widely used practice in the country. In this way, the current research aims to evaluate the effects of the sludge disposal in the performance, operation and maintenance of treatment plant of leachate from landfill of Anápolis (GO). The characterization of the municipality RST was also performed by analyzing of twelve composite samples, each one from five vacuum trucks. It was evaluated the system consists of two identical modules, one it was the control group and another one received the RST. This module was submitted, increasingly, to differents Rate Volumetric Application (RVA) of RTS. Thus, the study was divided into five phases, starting with RVA of 13 % up to 204 %. Various parameters (BOD, COD, pH, oil and grease, total phosphorus, ammoniacal nitrogen, suspended solids, settling solids and Escherichia coli) were analyzed for the samples from the influent and effluent of the anaerobic and facultative ponds. It was also evaluated the impact on the maintenance and operation in the system plant, by measuring the height of the sludge in anaerobic lagoon and quantification of scum formed on the surface anaerobic pond. In facultative ponds it was performed by raising the phytoplankton community, ordering to identify possible interference in the richness and abundance of algae and cyanobacteria in these ponds. The data were statistically analyzed by the Studentt test, and the results indicated that until to 18 % of RVA there were no significant changes in the quality of treated leachate (effluent of stabilization ponds). Since the RVA of 35 % was detected a significant difference in the concentration of E. coli and ammoniacal nitrogen in treated effluent (p < 0.05). At the RVA of 204% the concentration of phosphorus in the final effluent from facultative pond increased. There was an increase in sludge generation of 266% in the receiving anaerobic pond and only 38% in the control anaerobic pond. In addition, there was a thick layer of scum only on the surface of the receiving anaerobic pond. The phytoplankton community of facultative ponds was similar and presented low diversity. The Chlorella genera were dominant in both lagoons. From the results of this study, it is recommended the conjugate treatment of RFTS and leachate in stabilization ponds systems, because even applying RVA of 204%,the final effluent don’t have concentrations higher than those stipulated by CONAMA Resolution 430/2011.